Robot assisted "en bloc" radical nephrectomy, splenectomy and distal pancreatectomy for renal cell carcinoma: case report and illustration of technique. Issue 4 (December 2016) - Abdul-Muhsin, Haidar; Stern, Karen; Katariya, Nitin; Castle, Erik
Abstract A 57-year-old female presented with recurrent gross hematuria and a large left renal mass with solitary pancreatic metastasis. After thorough evaluation, an en bloc robot assisted radical nephrectomy, distal pancreatectomy and splenectomy was performed using a team-based approach between urologists and the transplant/hepatobiliary teams. A standard robotic nephrectomy approach was used with intraoperative ultrasound to determine the extent of pancreatic involvement. Left kidney, left adrenal gland, spleen and pancreatic tail were resected en bloc. Total operative time was 194 min. Perioperative Hemoglobin change was 2.3 g/dL. The final pathology demonstrated a 12.5 cm, Fuhrman grade 3, clear cell RCC along with a 2.5 cm pancreatic metastasis consistent with pT3a, N0, M1 with negative surgical margins. The patient was discharged on post-operative day three and experienced no postoperative complications. This case report highlights the feasibility of this procedure and calls for evaluation of surgical outcomes in this disease category.